The Effect of the Abuses of Sidewalks on Walkability in the Residential Areas of Sulaimaniyah City - Younis, Mayada H.; Ali, Amjad M.; Towfeeq, Hawar T. (Sulaimani Journal for Engineering Sciences, 2019)
The sidewalk has a great importance as a key component and main complement to roads and streets in the cities generally and residential areas and neighborhoods in particular. These sidewalks constitute the main walking environment in the residential neighborhoods and the link between houses and residential buildings on one hand, and the streets and corridors of vehicles' movements on the other hand. In order to improve the walking environment in the residential areas, the specifications and the designs of these sidewalks should meet various requirements for the pedestrians, including the sense of safety, comfort and ease of movement. Many of residential areas in Iraqi cities suffer from weak sidewalks design, which has led to deterioration of the ability of walking on .This research attempts specifically to study the condition of sidewalks in some of the residential areas in the city of Sulaimani; focuses on the problem of poor sidewalks' conditions in the residential areas in general and the inability to use for safely walking in particular. Assuming that the non-compliance with the municipal regulations and abusing them by the users are the main reasons for the deterioration of sidewalks' conditions and inadequacy for walking. The research aims to find out the extent of the impact of these violations in disrupting the ability to walk in those pathways. The study methodology is a field surveying for the current state of sidewalks in these residential areas and comparing them with the available international standards and municipal regulations.
Keywords: Sidewalks; abuses; Sulaimania; pathways; walkability